2017
DOI: 10.1371/journal.pone.0175372
|View full text |Cite
|
Sign up to set email alerts
|

Examination of an eHealth literacy scale and a health literacy scale in a population with moderate to high cardiovascular risk: Rasch analyses

Abstract: IntroductionElectronic health (eHealth) strategies are evolving making it important to have valid scales to assess eHealth and health literacy. Item response theory methods, such as the Rasch measurement model, are increasingly used for the psychometric evaluation of scales. This paper aims to examine the internal construct validity of an eHealth and health literacy scale using Rasch analysis in a population with moderate to high cardiovascular disease risk.MethodsThe first 397 participants of the CONNECT stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
90
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 33 publications
15
90
0
2
Order By: Relevance
“…12,22,28 This was also concluded in the initial work by Norman and Skinner. 16 On the other hand, several studies have also shown an inherent structure with two 12,19,23,24 or three 12,30 factors reflecting the underlying content of electronic health literacy, as previously described.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…12,22,28 This was also concluded in the initial work by Norman and Skinner. 16 On the other hand, several studies have also shown an inherent structure with two 12,19,23,24 or three 12,30 factors reflecting the underlying content of electronic health literacy, as previously described.…”
Section: Introductionmentioning
confidence: 55%
“…This result is in line with total eHEALS scores reported in other studies. For instance, Richtering et al 19 reported a total eHEALS score of M=27.1 in a study including patients at risk of developing cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations